Management of groundwater abstraction and seawater intrusion in the Moghra aquifer, Egypt - Asaad M. Armanuos; Martina Zeleňáková; Ahmed Shalby; Sobhy R. Emara; Abdelazeim Negm (Scientific Reports)
Abstract Groundwater is being utilized as a major freshwater resource in numerous nations across the world, particularly in arid and semi-arid countries like Egypt. The main objective of this study is to simulate the impact of groundwater abstraction and saltwater intrusion in the Moghra aquifer using MODFLOW and SEAWAT. Various abstraction rate scenarios from wells were modeled for a 100-year cultivation project period to study the impact of abstraction on aquifer drawdown. For 1000 wells, the maximum simulated drawdown equals 54, 66, 85, and 100 m for the abstraction rates of 1000, 1250, 1500, and 1750 m3/day/well, which represents about 18%, 22%, 28%, and 30% of the saturated Moghra aquifer thickness, respectively. The consequence of increasing the abstraction rate is substantial on seawater intrusion in the Moghra aquifer. The concentration line of 3500 mg/L intruded inland into the Moghra aquifer to a distance of 30.7, 52.7, and 57.1 km in the eastern, central, and western parts, respectively. Increasing the rate of abstraction from 1000 to 1750 m3/day/well led to the advance of the seawater (3500 mg/L) inland to the Moghra aquifer by a distance of 0.6, 5.6, and 4.4 km in the eastern, central, and western parts, respectively. Between the proposed controlling methods, artificial recharge, in conjunction with saline water abstraction, has a significant impact on attenuating the seawater back to the seaside compared with each method alone. The outcomes of this study can be used for developing groundwater resources in both arid and semi-arid areas in a sustainable manner.